Frontispiece: Aromatic Fused [30] Heteroannulenes with NIR Absorption and NIR Emission: Synthesis, Characterization, and Excited‐State Dynamics. Issue 24 (1st June 2016) - Mallick, Abhijit; Oh, Juwon; Kim, Dongho; Rath, Harapriya
Abstract : Fused Heterocycles Recent developments in many different fields of modern science and medicine, such as molecular biology, material science, drug discovery, and tissue diagnostics have fueled the design of new chromophores that can absorb and/or emit within the red or NIR region. In their Communication onpage 8026 ff., H. Rath et al. describe the inclusion of fused thiophene moieties into the macrocyclic conjugation pathway, which triggered molecular rigidity leading to the isolation of first ever flat [30] heteroannulenes exhibiting an evident diatropic ring current endowed with NIR absorption and emission.